2004
DOI: 10.1196/annals.1308.060
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ethanol on Spatial and Nonspatial Memory in Adolescent and Adult Rats Studied Using an Appetitive Paradigm

Abstract: Adolescent rats have been reported to be less sensitive than adults to many acute ethanol effects, including ethanol-induced sedation and motor impairment, but conversely more sensitive to ethanol-induced disruptions in spatial memory in a Morris water maze (Markwiese et al., 1998). The present study examined adolescent and adult rats trained for 6 days under spatial or nonspatial versions of a presumably less stressful sand box maze. Moderately food-deprived animals were given 0, 0.5, or 1.5 g/kg ethanol intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…The results from laboratory animal studies also demonstrate alcohol's impairing effects on cognition. Specifically, acute ethanol administration impaired hippocampus-dependent learning and memory in the Morris Water Maze (Markwiese et al 1998;Shimizu et al 1998;Matthews et al 2002;Berry and Matthews 2004), the radial arm maze (Matthews et al , 1999Vandergriff et al 1995;White et al 1997White et al , 1998, the sandbox maze (Rajendran and Spear 2004), and contextual fear conditioning (see Table 2 for the summary of acute ethanol's effects on hippocampus-dependent learning and memory) (Melia et al 1996;Gould 2003b;Gould and Lommock 2003;Wehner et al 2004;Gould 2007, 2008).…”
Section: Alcoholmentioning
confidence: 99%
“…The results from laboratory animal studies also demonstrate alcohol's impairing effects on cognition. Specifically, acute ethanol administration impaired hippocampus-dependent learning and memory in the Morris Water Maze (Markwiese et al 1998;Shimizu et al 1998;Matthews et al 2002;Berry and Matthews 2004), the radial arm maze (Matthews et al , 1999Vandergriff et al 1995;White et al 1997White et al , 1998, the sandbox maze (Rajendran and Spear 2004), and contextual fear conditioning (see Table 2 for the summary of acute ethanol's effects on hippocampus-dependent learning and memory) (Melia et al 1996;Gould 2003b;Gould and Lommock 2003;Wehner et al 2004;Gould 2007, 2008).…”
Section: Alcoholmentioning
confidence: 99%
“…Adolescent rodents are more sensitive to the effects of acute and chronic ethanol on measures of locomotor stimulation, anxiety, ataxia, spatial memory, conditioned place preference, and social interaction as compared to adult rats (Hefner and Holmes 2007;Markwiese et al 1998;Philpot et al 2003;Rajendran and Spear 2004;Varlinskaya and Spear 2002;Yttri et al 2004). By contrast, other studies have shown that adolescent rodents are less sensitive than adult rats to the sedative and motor-impairing effects of ethanol, to ethanol-withdrawal-induced anxiety, and analgesia (Doremus et al 2003;Hefner and Holmes 2007;Silveri and Spear 1998;Varlinskaya and Spear 2002;White et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Numerous studies have investigated the effects of ETOH administration on animal models of learning and memory. In general, ETOH impairs spatial learning (Givens 1995;Matthews et al 2002;Boulouard et al 2002;Wright et al 2003;Gonenc et al 2005;Rajendran and Spear 2004), working memory (Gibson 1985;Melchior et al 1993;Givens and McMahon 1997;White et al 1997;Escher and Mittleman 2004), and avoidance (Bammer and Chesher 1982;Markel et al 1986;File and Mabbutt 1990;Melis et al 1996;Singh et al 2003) …”
Section: Introductionmentioning
confidence: 98%